PREPARATION AND CHARACTERIZATION OF PVA-SIO2 NANOCOMPOSITE MEMBRANES FOR SEAWATER DESALINATION BY PERVAPORATION: Original scientific paper - TIRNAKCI, BERK; SALT, YAVUZ (Chemical Industry & Chemical Engineering Quarterly, 2021)
Pervaporation is a membrane process that offers high separation performance and has an important potential for the treatment of saline water sources. In this study, poly(vinyl alcohol) (PVA) and PVA-SiO2 nanocomposite membranes were prepared by the solution-casting method, and pervaporative water desalination studies were carried out for synthetic seawater (35 g L-1) at 30, 40 and 50 °C. Effects of the temperatures and the incorporation of SiO2 on the pervaporation performance of polymeric nanocomposite membranes were investigated. Membranes were characterized by scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FT-IR) and thermogravimetric analysis (TGA). In experiments conducted at 50 °C, a permeate flux of 4.93 kg m-2 h-1 with a salt rejection of 99.3% were obtained. The highest salt rejection was 99.8% at temperature of 30 °C. The results showed that the pervaporation performance of PVA membranes was remarkably enhanced with the incorporation of nano-SiO2 into polymeric matrix.